Engine performance analysis and improvement for a formula SAE (FSAE) racing car - Chiong, Meng Soon, 1987-; Srithar Rajoo, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2010